TEACHING STUDENTS IN MATH CIRCLES TO SOLVE CERTAIN EQUATIONS BY BRINGING THEM INTO A SYSTEM OF EQUATIONS - A. Turg’unov, M. Asqaraliyeva (Galaxy International Interdisciplinary Research Journal, 2022)
This article covers the methods of solving some equations by introducing them into a system of powerful equations equal to it, and provides examples of them.